PENGARUH KUALITAS LAYANAN TERHADAP LOYALITAS PELANGGAN KANTOR POS MADIUN - Yaumi Sa’adah (FIPA : Forum Ilmiah Pendidikan Akuntansi, 2014)
This study aims to analyze the influence of service quality on customer loyalty postal services in Post Office covering 5 dimensions Madiun services consisting of physical evidence(Tangible), Reliability(Reliability), Responsiveness(reponsibility), Assurance(Assurance), and Empathy(empathy). Sampling technique in this study issimple random sampling with a sample of 245 people, using purposive sampling technique. In analyzing the data using SPSS version 16.0 for windows with multiple linear regression formula. Data collection using questionnaire and analyzed using T test and F test with a significant level of 0.05 or 5%. Respondents are customers with a minimum age of 20 years and never make adeal at least 2 times or more. Methods of data collectionin this study is the distribution of questionnaires. Analysis technique used is multiple linear regression. The results of hypothesis testing all variables (Tangible, Reliability, reponsibility, Assurance, Empathy) with an alpha value of 0.05 indicates a positive and significant effect on customer loyalty. The most powerful independent influence of the independent variable (customer loyalty) is variable Guarantee. Based on the partial test (T-test) showed that the value of the variable coefficient bail of 6,273. variable responsiveness of 3,316. variable reliability of 6187. variable direct evidence for 4705. and empathy variable for 2707